Characteristics and treatment strategies of aggressive angiomyxoma in women: A retrospective review of 87 cases - Wang, Yang; Bu, Xiaoling; Liu, Yanxia; Xing, Yu; Tong, Qing (Frontiers in Surgery, 2023)
Objective: Aggressive angiomyxoma (AAM) is a rare kind of soft tissue tumor. The purpose of this study was to summarize the clinical manifestations and treatment strategy of AAM in women. Method: We searched the case reports on AAM in EMBASE, Web of Science and PubMed, China biomedical database, Wanfang database, VIP database and China National Knowledge Internet from the database construction time to November 2022 without language restrictions. Then the obtained cases data were extracted, summarized and analyzed. Result: A total of 74 articles were involved including 87 cases. The age ranges of onset were 2 to 67 years. The median age at onset was 34 years old. The size of tumor varies greatly among individuals, and about 65.5% patients were asymptomatic. MRI, ultrasound and needle biopsy could help diagnose. Surgery was the main treatment, but it was prone to relapse. Gonadotropin releasing hormone agonist (GnRH-a) might be used to reduce the size of tumor before operation and prevent recurrence after operation. For patients that are unwilling to receive surgical treatment, GnRH-a alone could be tried. Conclusion: Doctors should consider the possibility of AAM in women with genital tumors. For surgery, ensuring the negative surgical margin is recommended for preventing recurrence, but we should not ignore the impact on excessive pursuit for negative margin on patient's reproductive function protection and postoperative recovery. The long-term follow-up is necessary regardless of whether patients receive medical treatment or surgical treatment.